The emergence of graphene and its nanomaterials based natural rubber nanocomposites: A short review on the latest trends on its preparations, properties and applications - Sharma Ashok Kumar S.; Nujud Badawi M.; Kandiah K.K.; Ramesh K.; Ramesh S.; Tiong S.K. (Elsevier B.V., 2025)
The two-dimensional (2D) graphene material has been a rising star in the area of polymer nanocomposites and materials science due to its excellent mechanical, electrical and thermal properties, gas barrier performance and high surface area. Hence, this makes graphene and its nanomaterials an ideal multifunctional filler for rubbers, which improved the overall properties of the natural rubber (NR) matrix. However, in order to tailor the interfacial interaction, appropriate graphene dispersion, the vulcanization kinetics etc., it is vital to carefully consider the utilization of the graphene properties in the rubber nanocomposites to yield high quality nanocomposites. This review offers the coverage on the recent methods and trends to uniformly disperse nanofillers in rubber matrix, to construct a strong interfacial interaction between the NR and graphene and the effects of graphene oxide (GO) and reduced GO (rGO) on the vulcanization behaviour of NR nanocomposites. The properties of these nanocomposites will be discussed to provide an intuition into the major necessities of graphene fillers with respect to several industrial applications. Finally, the challenges that need to be addressed in order to attain advanced device performance will be discussed along with the future perspectives. It is envisaged that the outstanding functional properties of the 2D fillers and their combinations could be exploited to fabricate graphene/NR nanocomposites, thus making it a potential candidate as a new class of advanced materials in the near future. ? 2024 Elsevier B.V.